Hubungan antara Adversity Quotient dengan Stres Akademik pada Mahasiswa Semester Akhir Universitas Islam Bandung - Iqlima Nurfadhila Aulia; Budiman, Agus (Bandung Conference Series: Psychology Science, 2024)
Abstract. Students are required to have critical thinking and be able to act quickly and precisely. Students will be faced with various demands and obstacles during the lecture process. These include coursework that must be completed at the same time, practicums, achievement of study load, and thesis up to the final semester stage. The various task demands faced can make students feel uncomfortable so they do not enjoy academic activities and have difficulty concentrating. The aim of the research is to describe adversity qoutient and academic stress in Final Semester Students at Bandung Islamic University and to find out how big the relationship is between adversity qoutient and academic stress among Final Semester Students at Bandung Islamic University. The research method is a quantitative research approach. The population used by researchers was 792 final semester students at Bandung Islamic University. A sample of 90 respondents filled out the Google form research questionnaire. So the researcher took everything as a research sample, namely 90 respondents. Based on the calculated T and calculated F, the Sig value is known. (2-tailed) between the two variables is 0.000, smaller than 0.05. So it can be concluded that there is a significant correlation or relationship between the Adversity Quotient variable and the academic stress variable in Final Semester Students at Bandung Islamic University. Abstrak.Mahasiswa dituntut memiliki pemikiran kritis dan dapat bertindak dengan cepat dan tepat. Mahasiswa akan dihadapkan dengan berbagai tuntutan maupun hambatan selama proses perkuliahan. Diantaranya tugas kuliah yang harus diselesaikan dalam waktu bersamaan, praktikum, pencapaian beban studi, hingga skripsi untuk ke tahap semester akhir. Berbagai tuntutan tugas yang dihadapi dapat membuat mahasiswa merasa tidak nyaman sehingga tidak menikmati kegiatan akademik dan sulit berkonsentrasi. Tujuan penelitian untuk gambaran adversity qoutient serta stres akademik pada Mahasiswa Semester Akhir Universitas Islam Bandung serta juga untuk mengetahui seberapa besar hubungan antara adversity qoutient dengan stres akademik pada Mahasiswa Semester Akhir Universitas Islam Bandung. Metode penelitian adalah pendekatan penelitian kuantitatif. Populasi yang digunakan peneliti sebesar 792 Mahasiswa Semester Akhir Universitas Islam Bandung Sampel 90 orang responden yang mengisi google form kuesioner penelitian. Maka peneliti mengambil semua menjadi sampel penelitian yaitu 90 orang responden. Berdasarkan T hitung dan F hitung diketahui nilai Sig. (2-tailed) antara kedua variabel adalah sebesar 0,000 lebih kecil 0,05. Sehingga dapat disimpulkan bahwa terdapat korelasi atau hubungan yang signifikan antara variabel Adversity Quotient dengan variabel stres akademik pada Mahasiswa Semester Akhir Universitas Islam Bandung.